Diskriminasi Sosial dan Marginalisasi Ekonomi sebagai Korelaktor Kejahatan: Studi Etnografi pada Komunitas Urban Poor di Jakarta, Surabaya, dan Medan - Taun, Taun; Giffari, Muhammad Naufal (Verdict: Journal of Law Science, 2025)
This study examines the complex relationship between social discrimination and economic marginalization as underlying drivers of criminal behavior among urban poor communities in Jakarta, Surabaya, and Medan. Utilizing a critical ethnographic methodology, the research explores how structural inequalities—rooted in institutional exclusion and persistent stigmatization—shape individual adaptation strategies that often result in involvement with criminal activities. Data were collected through in-depth interviews, participant observation over twelve months, and comprehensive analysis of police records and relevant policy documents. Evidence gathered from fieldwork demonstrates that restricted access to formal employment and essential public services perpetuates material deprivation, while cultural stigmatization reinforces negative social stereotypes and marginalizes urban poor further from opportunities for meaningful participation. Anchored in strain theory (Merton, 1938), conflict criminology, and frameworks of social exclusion, this study finds that criminality functions as a rational, adaptive response to survival challenges presented by systemic exclusion. The findings also highlight disparities in the criminal justice process, including over-policing, limited access to legal representation, and disproportionate punitive outcomes for poor individuals. By integrating empirical data and theoretical perspectives, the research argues for a reconceptualization of urban criminality as a social and structural phenomenon rather than individual pathology. Policy implications suggest a need for distributive justice reforms and inclusive social development programs to break the cyclical ties between discrimination, marginalization, and crime within Indonesian urban contexts. This study contributes to the field of criminology by providing grounded, context-specific analysis relevant for future intervention and policymaking.